Potential SARS-CoV-2 Preimmune IgM Epitopes - Shivarov, Velizar; Petrov, Peter K.; Pashov, Anastas D. (Frontiers in Immunology, 2020)
While studying the human public IgM igome as represented by a library of 224,087 linear mimotopes, three exact matches to peptides in the proteins of SARS-CoV-2 were found: two in the open reading frame 1ab and one in the spike protein. Joining the efforts to fast track SARS-CoV-2 vaccine development, here we describe briefly these potential epitopes in comparison to mimotopes representing peptides of SARS-CoV, HCoV 229E and OC43.